Changes in air and liquid permeability properties of loess due to the effect of lead contamination - Wen, Shaojie; Cheng, Wen-Chieh; Hu, Wenle; Rahman, Md Mizanur (Frontiers in Earth Science, 2023)
Heavy metals in landfill leachate are easily adsorbed by soil particles, causing serious threats to human health and surrounding environments. Mining and metallurgy activities are intensive in North-West China, thereby enlarging the threats. The aim of the present work is to enhance our knowledge regarding the linkage between the micro-structural evolution of the loess soil, induced by lead contamination, and the macro air and liquid permeability properties. A series of air and liquid permeability tests on the uncontaminated and Pb-contaminated loess specimens were conducted. Their air and liquid permeability properties were evaluated on the basis of the Darcy's law and the soil-water retention curves, respectively. The microstructural evolution, when subjected to low and high Pb 2+ concentrations, was assessed through scanning electron microscopy (SEM), X-ray diffraction (XRD), mercury intrusion porosimetry (MIP), and zeta potential tests. The intrusion of Pb 2+ decreases the absolute zeta potential ζ, which in turn leads to a more distinct agglomerated structure and higher intrinsic permeability. Moreover, the dedolomitisation and associated cerussite (PbCO3) precipitation are deemed as the main cause leading to clogging of the micropores, while the corrosion of the cement between soil particles by H + shows a good correspondence to an increase in the number of mesopores. With the concentration of Pb 2+ increasing from 0 mg/kg to 2000 mg/kg, the proportion of micropores decreases from 37.9% to 15.1% and the proportion of mesopores increases from 17.3% to 53.3%. In addition, the air entry value decreases from 19.5 kPa to 12.8 kPa, indicating the water retention behaviour decreased. The findings highlight the impacts of lead contamination on the microstructure and macro permeability properties and give some design guideposts to heavy metal-contaminated site remediation.